The Moral Reading of HIV Prevention in the United States: Criminal Law and Tort Law - Siradj Okta (Universitas Katolik Indonesia Atma Jaya, 2021)
The United States government has been campaigning to encourage people to take HIV testing and thus get treated. It is puzzling that more than 50% of States have HIV-specific criminal laws that criminalize both exposure and transmission. At the same time, there is an increased tort law to seek financial compensation for unwanted HIV exposure and transmission. While both laws the moral claim of protecting people from HIV infection, this paper is trying to find an answer to the following inquiry: What is the difference of the moral reading between the use of criminal law and tort law in addressing HIV prevention in the United States? This paper uses the traditional descriptive comparison between criminal law and tort law under the American legal system with a nationwide jurisdictional scope. This paper measures the difference using the frame of reference of Ronald Dworkin's law, morality, and interpretation theory. Both criminal law and tort law have been developing similar liability principles regarding HIV exposure and transmission under the United States' common law tradition. For HIV prevention itself, both criminal law and tort law play a marginal role in gaining public health purposes in reversing the HIV epidemic. Criminal law has been scrutinized as not aligned with the purpose of law where misconceptions exist in both substantive dimension and the underlying moral claim. Tort law, on the other hand, suffers an even less moral claim on public health purposes. However, tort law maintains a consistent narrow sense of financial liability.